Sugestões práticas para a descrição do EEG de rotina - Kanda, Raquel Guimarães; Cury, Ivan José [UNESP]; Lovatel, Arnaldo Thiago Berto; Kanda, Paulo Afonso Medeiros (My University, 2014)
A common complaint made by some referring physicians about the electroencephalogram (EEG) report is that it makes little sense and often does not help in the diagnosis or management of their patients. Thus, opening the topic for discussion, the authors, make brief comments and suggestions regarding the report of the EEG. A systematic approach to the description is required so that the findings contribute positively in the report process. Consequently, the description of the EEG should be divided into several parts: 1. laboratory and patient identification; 2. equipment technical characteristics and test conditions; 3. description of electroencephalographic findings; 4.Conclusion, which state that the examination is normal or not; 5. electroclinical correlations that is what matters to the requesting clinician, and it is the moment one attempts to confirm the clinical diagnostic hypothesis. This article advocates that the EEG report should be clear and seek electroclinical diagnosis because the EEG is a diagnostic tool for neurologists, clinicians, and pediatricians.
Practical suggestions for writing routine EEG reports
Keywords: Diagnosis; EEG; Electroencephalography; Methodology